Profitabilitas, Leverage, Kebijakan Hutang dan Kepemilikan Manajerial terhadap Nilai Perusahaan - Yoni Dwinatasari; Vidya Fahira; Jessi Charina Sembiring (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine and analyze the effect of profitability, leverage, debt policy, and managerial ownership on firm value. The type of data used is secondary data. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the 2017-2020 period with a total sample of 14 companies taken by the purposive sampling method. The data analysis method used is multiple linear regression analysis. The results showed, a) the variable return on assets has a tcount of 4.292 and a ttable of 2.016 with a significance of 0.00 <0.05; b) the current ratio variable has a tcount of -2.665 and a ttable of 2.016 with a significance of 0.01 <0.05; c) the variable debt to equity ratio has a tcount of 3.489 and a ttable of 2.016 with a significant value of 0.00 <0.05; d) the price earning ratio variable has a tcount of 2.981 and a ttable of 2016 with a significant value of 0.00 <0.05. In conclusion, simultaneously or simultaneously have a significant effect on firm value. Partially it is known that all independent variables namely profitability, leverage variables, debt policy variables and managerial ownership variables have significant and significant effect on firm value. Keywords: Debt Policy, Managerial Ownership, Leverage, Firm Value, Profitability